Fast Delayed Rectifier Potassium Current: Critical for Input and Output of the Circadian System - Kudo, Takashi (J Neurosci, 2011)
The ability to generate intrinsic circadian rhythms in electrical activity appears to be a key property of central pacemaker neurons and one essential to the function of the circadian timing system. Previous work has demonstrated that suprachiasmatic nucleus (SCN) neurons express the fast delayed rectifier (FDR) potassium current and raise questions about the function of this current. Here, we report that mice lacking both Kcnc1 and Kcnc2 genes [double knock-out (dKO)] fail to express the Kv3.1 and 3.2 channels in the SCN as well as exhibit a greatly reduced FDR current. SCN neurons from these dKO mice exhibit reduced spontaneous activity during the day as well as reduced NMDA-evoked excitatory responses during the night. Interestingly, the daily rhythm in PER2 expression in the SCN was not altered in the dKO mice, although the photic induction of c-Fos was attenuated. Behaviorally, the dKO mice exhibited extremely disrupted daily rhythms in wheel-running behavior. In a light/dark cycle, some of the dKO mice were arrhythmic, whereas others expressed a diurnal rhythm with low amplitude and significant activity during the day. When placed in constant darkness, the dKO mice exhibited low-amplitude, fragmented rhythms and attenuated light responses. Together, these data are consistent with the hypothesis that the FDR current is critical for the generation of robust circadian rhythms in behavior as well as the synchronization of the circadian system to the photic environment.